APPLICATION OF THE MOORA METHOD IN SELECTING THE BEST TEACHER AT SMK METHODIST 8 MEDAN - Arjon Samuel Sitio; Anita Sindar Ros Maryana Sinaga (INFOKUM, 2022)
Selection of the best teacher is not an easy thing to do by an institution or the management in a foundation. The selection of the best teacher is absolutely necessary so that the management can find out how far the teacher's level of knowledge isineducating students. A decision support system is a form of computer base information system (CBIS) that isinteractive, flexible and specifically developed to support the resolution of unstructured management problems to improve decision making. Decision support systems use data as input and with a process, produce output that will help decision makers. The MOORA method is a method that has calculations with minimum and very simple calculations. This method has a good level of selectivity in determining an alternative.